Hvad er det Grundtvigske? Refleksioner over en Nexø-disputats - Michelsen, William (Grundtvig-Studier, 1993)
What is the Grundtvigian? Reflections over an Nexø-dissertation. Henrik Yde: The Grundtvigian in Martin Andersen Nexøs life I-II. Copenhagen (Vindrose) 1991. Rewieved by William Michelsen